HUBUNGAN HARGA DIRI DENGANÂ KUNJUNGAN LANSIA KE POSYANDU LANSIA DI DESA KEJAPANAN KECAMATAN GEMPOL KABUPATEN PASURUAN - Zainuri, Imam; Rodiyahtul, Ike (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Decreased self-esteem of the elderly will affect the fulfillment of their activities include elderly to visit health control. The reality that case frequency visits to the elderly control decreased from year to year. This happens because the elderly feel embarrassed and reluctant to come to health center. The purpose of research to analisis the relationship of self-esteem with activeness elderly to visit health control. The researchdesignis analytic correlation with cross sectional approach. Variable research is self-esteemas independent variable and activeness elderly to visit health control. The population is all elderly in the Kejapanan village Gempol Pasuruan as many as 85 elderly. Samples were collected by total sampling. Data collected using questionnaires instrument for self-esteem and KMS to know activenees visit the elderly. Then processed by means of editing, coding, scoring and tabulating. The results showed of 47 respondents who have low self esteem is not active to visit health control as many as 38 respondents. And of 38 respondents have high self esteem actively visited Posyandu many as 26 respondents. These results show that the most high of self-esteem elderly, the most greater activity of the elderly to neighborhood health center visits. This occurs because the elderly who have high self-esteem have a response or a good adaptation in interaction and activity. The elderly is expected to increase knowledge about the benefits of Posyandu elderly so that they can be active in following the Posyandu.Keywords: Self-Esteem, Healh Control, Elderly